Gratitude and leave-taking: Editorial reflections, 2003–2017. Issue 4 (December 2017) - Layton, Lynne; Redman, Peter
Abstract In this article we reflect on our time as editors ofPsychoanalysis, Culture & Society. The article reviews some of the journal's major contributions to psychoanalytic understanding of social and political problems; considers whether or not we are entering a post-neoliberal world; and discusses some of the challenges faced byPCS given the marginal status of psychoanalysis in the wider culture, the journal's emphasis on interdisciplinarity, and its commitment to providing a space for multiple psychoanalytic voices. The article's later sections consider some of the areas that remain underdeveloped in the journal's coverage. In particular, the penultimate section explores the challenging task of specifying whether or not social entities, as opposed to individuals, can be said to have properties that are unconscious in the psychoanalytic sense.